Is Mixed Practice More Effective than Physical Practice Alone for the Acquisition of Non-dominant Side Kicking Performance? - Steel, Kylie A.; Ellem, Eathan (Frontiers in Psychology, 2016)
Perceiving and executing unfamiliar movements, such as left handed/footed movement skills in sports, places additional demands on the perceptual-cognitive system of players that may increase errors. The video self-modelling (VSM) method may provide an accessible solution to this issue, therefore the purpose of this study was to investigate the effect of the VSM method on the improvement of a non-preferred side kicking task. N=28 participants engaged in one of three conditions; Mirror reversed/ physical practice (PP), best-of/ PP, or physical practice only. Though not significant, data analysis indicated improved kicking accuracy for all groups, with VSM groups showing the most improvement. However, qualitative data revealed the ‘best-of’ group demonstrated more positive views toward their progress compared to other groups, and both VSM groups were more likely to attend to movement cues than target based cues. These trends may suggest merit for the use of VSM techniques, though its application and the source of mechanistic factors warrant further investigation.